The Influence of Leadership Style on Employee Performance and Loyalty Mediated by Organizational Climate - Tito Andrianto, Muhammad; Moeins, Anoesyirwan; Sunaryo, Widodo (Riviera Publishing, 2023)
In an increasingly complex and dynamic world of work, the role of leadership style, performance and employee loyalty are important aspects that need to be well understood. The Regional Immigration Office of the Ministry of Law and Human Rights in Jakarta has various duties and responsibilities, requiring effective leadership to achieve organizational goals. This study aimed to explore the relationship between leadership style, performance, and employee loyalty at the Regional Immigration Office of the Ministry of Law and Human Rights in Jakarta. This study used a Sequential Explanatory approach, which combined qualitative and quantitative methods. Data was collected through in-depth interviews and observations as qualitative methods to understand leadership style and organizational climate. Furthermore, a structured questionnaire was utilized to gather quantitative data about employees' perceptions of leadership style, performance, and loyalty. Qualitative data were analyzed using a thematic approach, while quantitative data were analyzed using statistical analysis. The study's results showed that leadership style influenced employee performance and loyalty. The organizational climate was also proven to mediate the effect of leadership style on employee performance and loyalty.